An introduction to mathematical cryptography - Hoffstein, Jeffrey; Pipher, Jill; Silverman, Joseph H. (Undergraduate texts in mathematics, 2014)
This self-contained introduction to modern cryptography emphasizes the mathematics behind the theory of public key cryptosystems and digital signature schemes. This text provides an ideal introduction for mathematics and computer science students to the mathematical foundations of modern cryptography. The book includes an extensive bibliography and index; supplementary materials are available online. The book covers a variety of topics that are considered central to mathematical cryptography.